Preparation and properties of PBAT/PLA composites modified by PVA and cellulose nanocrystals. Issue 2 (3rd August 2021) - Liu, Hailu; Chen, Ruilian; Sun, Xiaoyan; Li, Fayong; Shen, Huayan; Wang, Ke; Wang, Qing; Li, Yuan; Xie, Dong; Chen, Junjia
Abstract: Cellulose nanocrystal (CNC) was prepared through the hydrolysis of concentrated sulfuric acid using commercial bagasse pulp as a raw material. The performance of the developed CNC was tested through the atomic force microscope, particle size measurement, and zeta potential analysis. The melt blending method was adopted to prepare thermoplastic polyvinyl alcohol (TPVA) and CNC‐TPVA using the glycerol (GI)‐dicondensed triethylene glycol (TEG) complex. The TPVA and CNC‐TPVA were blended with poly(butylene adipate‐coterephthalate) and polylactic acid composite material (COM) through melt extrusion granulation and blown film, and then explored the effect of CNC on the UV aging properties of materials. The complex plasticizer could effectively break the PVA hydrogen bond and reduce its melting point. It had been observed that CNC had good interface compatibility with PVA, and CNC did not affect the crystallinity of PVA, but it could weaken the hydrogen bond between GI, TEG, and PVA, thereby reduce the plasticizing effect of PVA. Compared TPVA‐COM with CNC‐TPVA‐COM, detailed information of crystallization, the thermal stability of materials and mechanical properties was presented in the UV aging process, it was found that the cross‐section of CNC‐TPVA‐COM was rough, and its unevenness formed a striped structure, and its hydrogen bond strength, diffraction peak strength and anti‐aging performance were all improved. Abstract :